Pengaruh Berat Terhadap Luas Permukaan Hidrotalsit Dengan Metode BET dan t-PLOTE - Yusuf Habibi (UIN Sunan Kalijaga Yogyakarta, 2021)
An effect of mass to surface area in Hidrotalcite with BET and t-Plote methods has been studied. Surface Area Analyser Novatouch LX-4 was used for this studied. In this studies there is variation of mass in Hidrotalcite 0,0703g; 0,0637g; 0,0504g and 0,0413g. From weigth of mass have a result surface area with BET methods Hidrotalcite 12,1605m2/g; 7,29699m2/g; 5,41373m2/g and 1,51093m2/g. T-Plote methods result mikropore area 10,0791m2/g; 17,2148m2/g; 20,9804m2/g and 29,7217m2/g. These results show that more ligth of the mass Hidrotalcite, surface area decreased, but the mikropore area increased.